Hubungan Dukungan Keluarga dengan Risiko Depresi Postpartum - Ariyanti, Ririn (Jurnal Kebidanan Mutiara Mahakam, 2020)
The process of psychological adaptation in a mother has been started since the mother was pregnant. Pregnancy and childbirth are normal events in life, however many mothers experience significant stress in undergoing the process. Family responsibilities will increase with the presence of newborn babies. The encouragement and attention of other family members is positive support for the mother. Postpartum depression is a disorder that is really considered a psychopathology that most often precedes suicide, so it is not uncommon to end in death. Factors that influence the success of the transition to parenthood during the postpartum period are, respond to support from family and friends, The purpose of this study was to determine the relationship of family support with the risk of postpartum depression. This research is a quantitative study, with a cross sectional approach. The sample of this study was postpartum mothers who came to the Sleman Distirct Hospital totaling 110 respondents and the sampling technique uses quota sampling. The result of this study based on the chi squre statistical test results obtained a value (p-value) 0.413. The p-value is greater than Î± 0.05 so that there is no relationship between family support and the risk of postpartum depression. Postpartum depression is not only influenced by family support but also other factors such as employment, education, age and parity. For next research, they are expected to do more research by taking other variables that can influence postpartum depression.